Administrative Decentralization and Climate Change : Concepts, Experience, and Action - Smoke, Paul; Cook, Mitchell (World Bank, Washington, DC, 2022)
International and domestic efforts to respond to the severe global challenge of climate change are on the rise and evolving. Despite the importance of action from multiple levels of government, public sector reforms to address climate change and to promote decentralization and or intergovernmental relations tend to be designed and managed separately. Intergovernmental relations have administrative, fiscal, and political dimensions. This paper focuses on climate action at the subnational government level through administrative decentralization and intergovernmental collaboration. The Paris Agreement acknowledges the climate change-decentralization connection, noting a need for the engagement of all levels of government and various actors. The bottom line is that the appropriate mix of subnational climate actions will vary because climate change needs and feasible responses, as well as intergovernmental structures and the nature and degree of decentralization, differ across countries. The paper is organized as follows: section one gives introduction. Sections two and three, respectively, provide concise summaries of basic climate change issues and policies and the principles and practices of decentralization and intergovernmental relations. Section four covers the intersection of climate change action and decentralization. Section five reviews administrative decentralization for climate change action. Section six presents illustrative cases drawn from secondary materials to illustrate how selected administrative functions are used in specific situations and the types of interactions among them. Section seven concludes with some synthetic observations and offers general guidance on assessing the prospects for enhancing and supporting subnational administrative action on climate change.